2019
DOI: 10.1177/0886260519883866
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Violence Among Gender and Sexual Minority College Students: The Risk and Extent of Victimization and Related Health and Educational Outcomes

Abstract: A multisite survey conducted at eight campuses of a southwestern university system provides the data for the present study, total N = 17,039 with 1,869 gender and sexual minority (GSM) students. Sexual violence was measured using the Sexual Experiences Survey (SES), and analysis included both the participant’s risk of experiencing sexual violence and the extent (or total count) of sexual violence experienced. This study poses the following research questions: What effects do gender identity and sexual orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 51 publications
7
64
1
Order By: Relevance
“…The sexual assault of trans persons is an insidious problem, with trans persons experiencing high rates of victimization and serious psychosocial and health consequences that no single discipline or sector has the training or resources to address [4,6,8,9,11]. Our study further lays the foundation for an Ontario-wide intersectoral network of healthcare and community organizations that holds the potential to substantially enhance the response to trans survivors of sexual assault [24,25].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The sexual assault of trans persons is an insidious problem, with trans persons experiencing high rates of victimization and serious psychosocial and health consequences that no single discipline or sector has the training or resources to address [4,6,8,9,11]. Our study further lays the foundation for an Ontario-wide intersectoral network of healthcare and community organizations that holds the potential to substantially enhance the response to trans survivors of sexual assault [24,25].…”
Section: Discussionmentioning
confidence: 89%
“…In the recent cross-Canada Trans-PULSE survey, 26% of trans persons reported having been sexually assaulted in the previous five years [10]. Trans persons also experience high rates of poly-victimization and revictimization [2,9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of harassment was operationalized by calculating the sum of sexually harassing behaviors endured across all items separately for each scale (faculty/staff and peer, respectively) and for both scales combined (total). We described the study methodology and reported findings about the risk and extent of sexual violence and sexual harassment endured by students at academic institutions (Busch-Armendariz et al, 2017a; Kammer-Kerwick et al, 2019; Wood et al, 2018). We intentionally used extent instead of severity due to the subjective appraisal of severity (Cortina et al, 2002; Wright & Fitzgerald, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…College students in the United States are at high risk of experiencing sexual violence, with estimated prevalence rates of sexual assault since enrolling in college ranging from 14.2% to 23.1% among college women (Muehlenhard, Peterson, Humphreys, & Jozkowski, 2017). Gender and sexual minority students are at even higher risk for sexual assault; though the relative risk varies, gender and sexual minority students are up to approximately four times as likely to be victimized as their cisgender, heterosexual peers (Coulter et al, 2017; Kammer‐Kerwick et al, 2019). In addition to the negative psychological and physical consequences associated with experiencing sexual violence (e.g., Black, 2011), college survivors face negative academic consequences such as decreases in performance, higher stress, and greater likelihood of dropping classes or changing residences than non‐victimized peers (Banyard et al, 2017; Jordan, Combs, & Smith, 2014; Krebs et al, 2016).…”
Section: Introductionmentioning
confidence: 99%